Coastal vulnerability assessment in urban planning: a comparative tool-based selection approach for the Egyptian context - Aya Adel Hemida; Marwa Abo Elfetouh Khalifa; Morad Abdelsalheen; Samy Afifi (Renewable Energy and Sustainable Development)
In the context of coastal cities facing sea level rises (SLR) and climate extremes, this study seeks to provide Coastal Vulnerability Assessment (CVA) tools for improved urban planning in Egypt. Through comparative analysis and systematic application of exclusion criteria, we evaluated 16 tools to identify the most suitable options. The objective was to select tools that exhibit the greatest relevance and potential applicability to effectively address CVAs in the region. Among the analyzed tools, 37.5% appeared to align well with the context. CoVI is notably recommended due to its comprehensive dimension consideration. This approach improves coastal vulnerability understanding and aids planners in decision-making for coastal areas.   Received: 13 November 2023 Accepted: 09 February 2024 Published: 03 March 2024